Rational skepticism: A scientific review of Witts' (2018) criticisms of the PEAK relational training system. Issue 2 (25th October 2019) - Belisle, Jordan; Dixon, Mark R.
Abstract : Witts' (2018) review of the peer‐reviewed research on the PEAK‐Direct Training Module (Dixon, 2014) yielded a divergent conclusion from that of previous reviews (Reed & Luiselli, 2016; Dixon, Belisle, McKeel et al., 2017). Witts advocates for skepticism of this research due to methodological shortcomings, hyperclaiming of results, and inappropriate statistical testing procedures. We identified 30 criticisms in Witts' review, respond to each, and argue that all but 2 (7%) contain untrue assumptions (7, 23%), are not novel (5, 17%), are logically invalid (7, 23%), or are more appropriately framed as criticisms of applied behavior analytic research more generally (9, 30%). The two criticisms that support Witts' purpose in writing his review are minor and not fatal. We discuss all of Witts' criticisms both specifically and broadly to illustrate that most of his suggestions about applied behavior analytic research may actually serve to hinder progress in a discipline moving toward larger‐scale research.